Self‐Efficacy, Attitudes, and Choice of Strategies for English Pronunciation Learning. Issue 1 (23rd September 2017) - Sardegna, Veronica G.; Lee, Juhee; Kusey, Crystal
Abstract: This article proposes a structural model of English language learners' self‐efficacy beliefs, attitudes toward learning pronunciation skills, and choice of pronunciation learning strategies. Participants' responses ( N = 704) to two self‐reported questionnaires—Strategies for Pronunciation Improvement (SPI) inventory and Learner Attitudes for Pronunciation (LAP) inventory—were analyzed using structural equation modeling (SEM) to determine the direct and indirect relationships among the latent variables. The results showed that perceived practical and linguistic values related to pronunciation learning led students to be concerned about their pronunciation and thus increased their intentional behavior to improve their pronunciation skills. Also, the greater the intentional behavior, the more likely students were to select strategies to advance their pronunciation skills. Furthermore, a multigroup SEM analysis revealed that self‐efficacy about pronunciation skills significantly influenced girls' emotions, whereas self‐efficacy had a negligible effect on boys' emotions. Pedagogical implications of these findings and possible avenues for future research are discussed. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible via the Open Science Framework athttps://osf.io/6a3we . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .